Expression and rescuing of a cloned human tumour necrosis factor gene using an EBV-based shuttle cosmid vector. - Kioussis, D (1987)
A cosmid vector carrying the Epstein-Barr virus origin of replication, the EBNA-1 gene, the hygromycin phosphotransferase (hph) gene and pBR322 sequences has been constructed. This cosmid can replicate autonomously in the nucleus of human tissue culture cells, even when it carries a 35-kb long insert. The cosmid can be rescued from the transfected cells by cloning it directly into ampicillin-sensitive Escherichia coli. A gene for human tumour necrosis factor (TNF) cloned into this cosmid vector was introduced in tissue culture cells, where it was transcribed into mature mRNA.